Declining malaria transmission differentially impacts the maintenance of humoral immunity to plasmodium falciparum in children - Mugyenyi, Cleopatra K.; Elliott, Salenna; Osier, Faith (The journal of infectious diseases, 2017)
Declining malaria transmission results in reductions in total antibodies to merozoite antigens in children. However, some important functional antibodies and an
Gesehen am 22.08.2018